Interactive robots for health in Europe: Technology readiness and adoption potential - Östlund, Britt; Malvezzi, Monica; Frennert, Susanne; Funk, Michael; Gonzalez-Vargas, Jose; Baur, Kilian; Alimisis, Dimitris; Thorsteinsson, Freygardur; Alonso-Cepeda, Antonio; Fau, Guillaume; Haufe, Florian; Di Pardo, Massimo; et al. (Frontiers in Public Health, 2023)
Social robots are accompanied by high expectations of what they can bring to society and in particular in the healthcare sector. So far, promising assumptions have been presented about how and where social robots are most relevant. We know that the industry has used robots for a long time, but what about social uptake outside the industry, specifically, in the healthcare sector? This study takes a step further from speculation about what trends are discernible to better understand the gap between technology readiness and the adoption of interactive robots in the welfare and health sectors in Europe. An assessment of interactive robot applications at the upper levels of the Technology Readiness Level scale is combined with an assessment of adoption potential based on Rogers’ theory of diffusion of innovation. Most robot solutions are dedicated to individual rehabilitation or frailty and stress. Fewer solutions are developed for managing welfare services or public healthcare. The results show that while robots are ready from the technological point of view, most of the applications had a low score for demand according to the stakeholders. To enhance social uptake, a more initiated discussion, and more studies on the connections between technology readiness and adoption and use are suggested. Applications being available to users does not mean they have an advantage over previous solutions. Acceptance of robots is also heavily dependent on the impact of regulations as part of the welfare and healthcare sectors in Europe.